Incorporating digitally derived endpoints within clinical development programs by leveraging prior work - Amy Bertha; Rinol Alaj; Imein Bousnina; Megan K. Doyle; Danielle Friend; Rasika Kalamegham; Lauren Oliva; Igor Knezevic; Frank Kramer; Hans-Peter Podhaisky; Sven Reimann (npj Digital Medicine, 2023)
Digital health technologies (DHTs) enable remote data collection, support a patient-centric approach to drug development, and provide real-time data in real-world settings. With increasing use of DHTs in clinical care and development, we expect a growing body of evidence supporting use of DHTs to capture endpoint data in clinical trials. As the body of evidence grows, it will be critical to ensure that available prior work can be leveraged. We propose a framework to reuse analytical and clinical validation, as well as verification data, generated for existing DHTs. We apply real life case studies to illustrate our proposal aimed at leveraging prior work, while applying the V3 framework (verification, analytical validation, clinical validation) and avoiding duplication. Utilizing our framework will enable stakeholders to share best practices and consistent approaches to employing these tools in clinical studies, build on each other’s work, and ultimately accelerate evidence generation demonstrating the reproducibility and value add of these new tools.